Student Voices Following Fieldwork Failure: A Phenomenological Inquiry - Krusen, Nancy (International Journal of Practice-based Learning in Health and Social Care, 2015)
Clinical education, or fieldwork, is a required part of learning in many healthcare professions. Successful fieldwork indicates readiness for practice. Failure during clinical education has seldom been examined from the viewpoint of the student. The purpose of the study is to investigate adaptive strategies following fieldwork failure of occupational therapy students in the United States, to understand the meaning associated with the experience, and contribute to professional clinical education. This phenomenological study examines failure with an Occupational Adaptation perspective. Data are collected through open-ended, semi-structured interviews. Twelve occupational therapy students reveal a broad range of adaptive behaviours, strategies and categories without a predominant pattern. Three themes emerge: I need to tell my story not passing is not the same as failing, and convergence, supporting the concept of learning from what goes wrong. When academic or clinical education challenges are greater than a student’s ability to adapt, he or she may fail. The investigator recommends the inclusion of student voices for research in teaching and learning about failure. Future research could apply the Occupational Adaptation theoretical frame of reference to name and frame adaptive strategies in clinical education and intervention across professions and cultures that support professional growth.